Soft Religiosity Message for Indonesia from Soedjatmoko - Aji Dedi Mulawarman (Yayasan Rumah Peneleh, 2019)
This article tackles the thought of Soedjatmoko as one of Indonesian self-taught intellectuals. Through his writing “Human Dimension in Development”, “ Socialist Culture”, and “Asia in the Eyes of Soedjatmoko”, an evolution of his thought from socialist' historical materialism towards soft religiousity could be portrayed. It is concluded that integrity and intellectual bravery are the strength of the Indonesian that are derived from faith and tawhid. The spirit that Islam carries becomes the root of solution for poverty as well as applicable education for many countries, especially in Asia.